Answer:
or ![x=\frac{-7+ \sqrt{5}}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-7%2B%20%5Csqrt%7B5%7D%7D%7B2%7D)
Step-by-step explanation:
The given equation is
![(2x+3)^2+8(2x+3)+11=0](https://tex.z-dn.net/?f=%282x%2B3%29%5E2%2B8%282x%2B3%29%2B11%3D0)
Let us treat this as a quadratic equation in
.
where ![a=1,b=8,c=11](https://tex.z-dn.net/?f=a%3D1%2Cb%3D8%2Cc%3D11)
The solution is given by the quadratic formula;
![(2x+3)=\frac{-b\pm \sqrt{b^2-4ac} }{2a}](https://tex.z-dn.net/?f=%282x%2B3%29%3D%5Cfrac%7B-b%5Cpm%20%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D)
We substitute these values into the formula to obtain;
![(2x+3)=\frac{-8\pm \sqrt{8^2-4(1)(11)} }{2(1)}](https://tex.z-dn.net/?f=%282x%2B3%29%3D%5Cfrac%7B-8%5Cpm%20%5Csqrt%7B8%5E2-4%281%29%2811%29%7D%20%7D%7B2%281%29%7D)
![(2x+3)=\frac{-8\pm \sqrt{64-44} }{2}](https://tex.z-dn.net/?f=%282x%2B3%29%3D%5Cfrac%7B-8%5Cpm%20%5Csqrt%7B64-44%7D%20%7D%7B2%7D)
![(2x+3)=\frac{-8\pm \sqrt{20} }{2}](https://tex.z-dn.net/?f=%282x%2B3%29%3D%5Cfrac%7B-8%5Cpm%20%5Csqrt%7B20%7D%20%7D%7B2%7D)
![(2x+3)=\frac{-8\pm2\sqrt{5} }{2}](https://tex.z-dn.net/?f=%282x%2B3%29%3D%5Cfrac%7B-8%5Cpm2%5Csqrt%7B5%7D%20%7D%7B2%7D)
![(2x+3)=-4\pm \sqrt{5}](https://tex.z-dn.net/?f=%282x%2B3%29%3D-4%5Cpm%20%5Csqrt%7B5%7D)
or ![(2x+3)=-4+ \sqrt{5}](https://tex.z-dn.net/?f=%282x%2B3%29%3D-4%2B%20%5Csqrt%7B5%7D)
or ![2x=-3-4+ \sqrt{5}](https://tex.z-dn.net/?f=2x%3D-3-4%2B%20%5Csqrt%7B5%7D)
or ![2x=-7+ \sqrt{5}](https://tex.z-dn.net/?f=2x%3D-7%2B%20%5Csqrt%7B5%7D)
or ![x=\frac{-7+ \sqrt{5}}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-7%2B%20%5Csqrt%7B5%7D%7D%7B2%7D)
Answer:
A=96% B=86%
Step-by-step explanation:
brainlist will be welcomed :))
Answer:
x = y
Step-by-step explanation:
x/3 + x/6 = 7/2
2x + x = 21
3x = 21
(divide 3 on both sides)
x = 7
Answer:
D
Step-by-step explanation:
you first have to find the domain by finding where the expression is defined
so the answer would be x>5